Converging integration between ascending proprioceptive inputs and the corticospinal tract motor circuit underlying skilled movement control. Issue 19 (February 2021) - Kalambogias, John; Yoshida, Yutaka
Abstract : Converging interactions between ascending proprioceptive afferents and descending corticospinal tract projections are critical in the modulation and coordination of skilled motor behaviors. Fundamental to these processes are the functional inputs and the mechanisms of integration in the brain and spinal cord between proprioceptive and corticospinal tract information. In this review, we first highlight key connections between corticospinal tract motor circuit and spinal interneurons that receive proprioceptive inputs. We will also address corticospinal tract access to the presynaptic inhibitory system in the spinal cord and its role in modulating proprioceptive stimuli. Lastly, we will focus on the corticospinal neuron influences on the dorsal column nuclei complex, an integration hub for processing ascending somatosensory information.